The role of hormone therapy in urogenital health after menopause. Issue 6 (December 2021) - Nappi, Rossella E.; Cucinella, Laura; Martini, Ellis; Cassani, Chiara
Abstract : Menopause represents an endocrine challenge to urogenital health, as oestrogens deprivation and androgens decline significantly contributes to age-related involution of vulvovaginal tissues and lower urinary tract. Genitourinary syndrome of menopause (GSM) is a clinical entity including the chronic and progressive condition of vulvovaginal atrophy (VVA) and encompassing both anatomical and functional consequences of menopause. The term GSM describes genital, sexual and urinary symptoms with a detrimental impact on quality of life (QOL). Several treatment options are available, but many barriers are still present to adequately diagnose and treat GSM. This review aims to present current evidences about epidemiology, aetiology, diagnosis and treatment of GSM, with a focus on prescription medications [low-dose local oestrogen therapy (LET), prasterone (DHEA) and the SERM ospemifene] for urogenital symptoms in healthy postmenopausal women and in special populations, including women with premature ovarian insufficiency (POI) and breast cancer survivors (BCS).